Buspirone administration: Influence on growth, spawning, immune response, and stress in female goldfish (Carassius auratus) - Hamed Abdollahpour; Naghmeh Jafari Pastaki; Milad Karimzadeh; Hosseinali Zamani (Heliyon)
The current study evaluated the impact of buspirone supplementation on the growth, physiology, stress response, spawning, and immunity in female goldfish (Carassius auratus). For this purpose, buspirone was dissolved in absolute methanol and sprayed onto the feed to create four experimental groups: B0 (control), B25 (25 mg kg−1), B50 (50 mg kg−1), and B100 (100 mg kg−1). Fish were fed their respective diets for 56 days and subjected to stress using the air exposure method at the end of the experiment. Growth performance analysis revealed that fish in the B100 group exhibited significantly higher final weight, weight gain, specific growth rate, and average daily gain than the other groups (P < 0.05). Plasma stress response indicated that cortisol levels were significantly lower in the B100 group after stress exposure, accompanied by a simultaneous decrease in glucose levels. The mucus stress response also showed lower cortisol and glucose levels in the B100 group compared to the other groups. Immunological analysis revealed significant increases in total protein, albumin, complement C3 and C4, and immunoglobulin M concentrations in both plasma and mucus of the B100 group (P < 0.05). Reproductive performance showed a notable enhancement in the number of eggs, fertilization rate, hatching rate, and survival rate in the B100 group compared to other groups (P < 0.05). Buspirone at higher concentrations, positively impacted various physiological aspects of goldfish, including growth, stress, immune activity, and reproductive performance. The significant improvements observed in growth parameters, cortisol levels, immunological markers, and reproductive outcomes suggest the potential of buspirone supplementation as a beneficial strategy in aquaculture practices.